Advancing ESP Material Development: An Analytical Approach Using 4D Models - Meli Fauziah (English Department - University of Sultan Ageng Tirtayasa, 2025)
This research aims to make teaching materials for Management Students of the Faculty of Islamic Economics and Business UIN Sunan Gunung Djati Bandung. This research uses a research and development (R&D) approach with a 4D (Define, Design, Develop, and Disseminate) model. A total of 78 students and experts from ESP teachers were taken as research samples. The results of the study show that the 4D model can produce relevant, organized and effective ESP material in the context of management. For this reason, the product is considered to have met the requirements for efficacy, practicality, and validity, so the product can be used after revision. Suggestions for further research on integrating digital technology into ESP instruction to improve student engagement and accessibility.